2022
DOI: 10.3389/fphar.2022.874474
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Properties of Mushroom Polysaccharides can Potentially Mitigate Oxidative Stress, Beta-Cell Dysfunction and Insulin Resistance

Abstract: Diabetes mellitus is a prevalent metabolic and endocrine illness affecting people all over the world and is of serious health and financial concern. Antidiabetic medicine delivered through pharmacotherapy, including synthetic antidiabetic drugs, are known to have several negative effects. Fortunately, several natural polysaccharides have antidiabetic properties, and the use of these polysaccharides as adjuncts to conventional therapy is becoming more common, particularly in underdeveloped nations. Oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 178 publications
0
16
0
Order By: Relevance
“…The phytochemical discoveries have led to the discovery of active substances in plants used in traditional remedies and to rely on them in the manufacture of a large proportion of medicines of plant origin 41 . Mushrooms are naturally capable of accumulating minerals and vitamins, as well as a variety of secondary metabolites including organic acids, alkaloids, phenols, and terpenoids 42 . Mushroom polysaccharides differ from other types of polysaccharides in regards to molecular weights, chemical characteristics, degree of branching, skeleton lengths, three-dimensional orientation, and other properties 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical discoveries have led to the discovery of active substances in plants used in traditional remedies and to rely on them in the manufacture of a large proportion of medicines of plant origin 41 . Mushrooms are naturally capable of accumulating minerals and vitamins, as well as a variety of secondary metabolites including organic acids, alkaloids, phenols, and terpenoids 42 . Mushroom polysaccharides differ from other types of polysaccharides in regards to molecular weights, chemical characteristics, degree of branching, skeleton lengths, three-dimensional orientation, and other properties 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this would entail overcoming the obstacles connected with their formulation development so that they can be recognized as nutraceuticals and reach patients with diabetes and other metabolic illnesses at the bedside. The many studies and discussions on mushroom polysaccharides described and suggested that antioxidant-active mushroom polysaccharides should be explored further and that their development as therapeutic agents in the treatment of diabetes should be supported [ 134 ].…”
Section: Challengesmentioning
confidence: 99%
“…However, the evaluation of scavenging activities in vitro is not a fully valid proof to claim the antioxidant effects of the polysaccharides because the scavenging activities investigations cannot simulate the interaction of antioxidants with chemical free radicals in the internal conditions of cells in a complex organism ( 45 ). Interestingly, numerous in vivo studies have shown that mushroom polysaccharides are capable of protecting the antioxidant activities of enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px), which are major components of the defense system against ROS within body ( 20 ). For instance, oral administration of Tremella fuciformis polysaccharides (TFPS) markedly improved the SOD and GSH-Px activities in serum, liver, and heart tissues in D-galactose-induced aging mice ( 46 ).…”
Section: Biological Mechanisms Of Mushroom Polysaccharides On Anti-di...mentioning
confidence: 99%
“…The potential applications of mushroom polysaccharides in diabetic complications have also been proposed by researchers ( 19 ). Additionally, mushroom polysaccharides ameliorating oxidative stress, beta-cell dysfunction, and insulin resistance, which are closely associated with DM, through antioxidant action have been discussed recently ( 20 ). In this review, the extraction methods of mushroom polysaccharides, and mushroom polysaccharides with potentials in the management of DM reported in recent 3 years were summarized; the biological mechanisms including anti-oxidation, hypolipidemia, anti-inflammation, and modulating gut microbiota in anti-diabetes, and future perspectives were also discussed for a better understanding the current status of knowledge in such fields and providing a valuable reference for the development and application of mushrooms polysaccharides in functional foods and nutraceuticals for DM and its complications management.…”
Section: Introductionmentioning
confidence: 99%